Tar reduction in biomass syngas using heat exchanger and vegetable oil bubbler. (15th May 2019) - Thapa, Sunil; Indrawan, Natarianto; Bhoi, Prakashbhai R.; Kumar, Ajay; Huhnke, Raymond L.
Abstract: A heat exchanger and vegetable oil bubbling system was designed and tested for biomass-generated syngas cooling and cleaning. The fully enclosed heat exchanger contained water at 15 °C, with syngas having to travel 35 m 3 /s. Using canola oil, the bubbler was tested at 70 and 100 mm oil depths and 5 and 10 mm syngas bubble sizes to determine the effect of tar removal. The results showed that tar removal efficiency was significantly affected by oil depth and bubble size; however, the interaction between bubble size and oil depth was not significant. About 60% of tars was removed by the heat exchanger alone and 96% of the remaining tars was removed by the oil bubbler when used in series with the heat exchanger. Overall, tar reduction efficiency of 98.5% was achieved with the heat exchanger plus oil bubbler having oil depth of 100 mm and syngas bubble size of 5 mm. Heat exchanger removed most of the tars by cooling the syngas below its dew point but syngas tars with low dew point was absorbed in the oil bubbler. Highlights: Tar removal efficiency of a heat-exchanger and an oil-bubbler was investigated. Effects of oil depths and bubble sizes of the bubbler on tar removal was studied. Heat exchanger alone removed about 60% of tars. 96% of the remaining tars was removed by the oil bubbler. Cooling syngas with heat exchanger and small bubble sizes increased tar removal.